Cubic Extensions of Flag-Transitive Planes, I. Even Order - Yutaka Hiramine; Vikram Jha; Norman L. Johnson (International Journal of Mathematics and Mathematical Sciences)
The collineation groups of even order translation planes which are cubic extensions of flag-transitive planes are determined.